Brain tumour mimics and chameleons. Issue 6 (20th September 2013) - Bradley, David; Rees, Jeremy
Abstract : The timely diagnosis of a brain tumour is crucial to optimising outcome in a group of patients with limited survival. Several common neurological conditions mimic brain tumours, causing concern to patient and physician until the correct diagnosis becomes clear. In addition, atypical presentations of brain tumours may cause diagnostic confusion, acting as chameleons and delaying correct workup and treatment. This review focuses on the important mimics and chameleons encountered in clinical practice, aiming to illustrate the wide range of clinical neurology encountered in this specialty and to provide guidance on reaching the correct diagnosis.